Exploring Intermolecular Interactions of L-Isoleucine in Aqueous Magnesium Nitrate and Magnesium Sulphate Solutions Across Temperature Variations (Journal of Scientific Research, 2025)
Acoustic and volumetric studies were conducted on aqueous solutions of L-isoleucine in the presence of magnesium nitrate and magnesium sulphate solution at temperatures of 288.15K and 298.15K. Ultrasonic sound waves propagating through these experimental solutions demonstrated a direct association between the different molecular interactions among the solution's constituents, both strong and weak. The rising electrostriction of water molecules around the solute and co-solute ions decreased isothermal compressibility (KT). Significant ion-ion, ion/hydrophilic-hydrophilic, and ion/hydrophobic-hydrophobic interactions happened among various segments of solute and co-solute ions, while ion-solvent interactions dominated. The processes of solvation and ion association brought about the reformation of the water structure. Numerous variables were assessed and highlighted the increased ion-solvent interactions, ion-pair formation, and structure-building capabilities of L-isoleucine in the presence of MgSO4 / Mg(NO3)2.